2022
DOI: 10.3389/fnins.2021.806260
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Adaptive Immune Responses in Central Nervous System Health, Aging and Diseases

Abstract: The field of neuroimmunology endorses the involvement of the adaptive immune system in central nervous system (CNS) health, disease, and aging. While immune cell trafficking into the CNS is highly regulated, small numbers of antigen-experienced lymphocytes can still enter the cerebrospinal fluid (CSF)-filled compartments for regular immune surveillance under homeostatic conditions. Meningeal lymphatics facilitate drainage of brain-derived antigens from the CSF to deep cervical lymph nodes to prime potential ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 277 publications
(383 reference statements)
0
20
0
Order By: Relevance
“…Barcik et al, 2016;Blasco et al, 2020;Yamada et al, 2020 Treatment with an anti-TREM2 agonist antibody has been shown to promote microglia activation and induce phagocytosis of amyloid in murine models of β-amyloidosis, reducing the amount of amyloid plaques and neuronal damage (Wang et al, 2020). Anti-amyloid and tau protein autoantibodies are naturally present in the serum and cerebrospinal fluid of Alzheimer's disease patients (Rickenbach and Gericke, 2022) and should be expected to after cerebral ischemia. A potential neuroprotective role and a relationship between autoantibody levels and the progression of brain neurodegeneration following ischemia are to be expected.…”
Section: Post-ischemic Pathology Of the Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Barcik et al, 2016;Blasco et al, 2020;Yamada et al, 2020 Treatment with an anti-TREM2 agonist antibody has been shown to promote microglia activation and induce phagocytosis of amyloid in murine models of β-amyloidosis, reducing the amount of amyloid plaques and neuronal damage (Wang et al, 2020). Anti-amyloid and tau protein autoantibodies are naturally present in the serum and cerebrospinal fluid of Alzheimer's disease patients (Rickenbach and Gericke, 2022) and should be expected to after cerebral ischemia. A potential neuroprotective role and a relationship between autoantibody levels and the progression of brain neurodegeneration following ischemia are to be expected.…”
Section: Post-ischemic Pathology Of the Brainmentioning
confidence: 99%
“…An imbalance in the production and removal of amyloid from the brain following ischemia indicates that the brain favors the pathological process of amyloid aggregation ( Pluta et al, 1994a , 2009 ; Pluta, 2000 ). Since the interstitial fluid, cerebral spinal fluid contributes to amyloid removal, amyloid and tau protein can be observed in both cerebral spinal fluid and peripheral blood serum ( Pluta et al, 2011 ; Rickenbach and Gericke, 2022 ). In the brain, amyloid is locally degraded by enzymes in cells residing in the brain, including microglia and astrocytes, which help to reduce the amyloid load in the brain ( Rickenbach and Gericke, 2022 ).…”
Section: Post-ischemic Pathology Of the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Key features of complex systems are unexpected dynamic and unexpected outcomes of interventions, called ‘emergent behavior’, bifurcation (or tipping) points where a division into branches or sub-groups occurs, i.e., fractal behavior, and unrealized multiple equilibria or steady states [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The population dynamics of pathogens and pathogen-host interactions depend on multiple factors, including natural and anthropogenic factors, along with other hidden factors, and are often underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…While the nervous system was originally considered an immune privileged site, combined observations from human and animal studies have strongly pointed toward an autoimmune origin for numerous diseases affecting the central nervous system (CNS) as well as the peripheral nervous system (PNS), such as multiple sclerosis (MS) and Guillain Barrè Syndrome (GBS) [ 12 ]. In addition, autoreactive immune responses have been recently described in other neurodegenerative disorders, namely, Parkinson's and Alzheimer's diseases, whose pathology has long been assumed to be merely due to intrinsic neuronal degeneration [ 13 , 14 ]. Autoimmunity is also believed to play a role in sleep disorders, epilepsy and neuropsychiatric diseases [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%